Enhancing integrated reporting quality through boardroom diversity: the critical role of board diligence in the petroleum industry - Ally Adam Mshana; Siasa Issa Mzenzi; Said Juma Suluo (Cogent Business & Management)
This study examines the influence of boardroom diversity and board diligence on Integrated Reporting (IR) quality in the petroleum industry, utilizing a sample of 500 firm-year observations from 100 companies from the Forbes Global 2000 list between 2018 and 2022. Employing panel data analysis with Feasible Generalized Least Squares (FGLS) regression models, we find that board gender and nationality diversity positively impact IR quality. In contrast, age diversity exerts a negative influence. Board diligence emerges as a crucial moderator, amplifying the positive effects of gender diversity and the negative impact of age diversity. These findings highlight the importance of diverse and actively engaged boards in fostering transparency, accountability, and stakeholder engagement, culminating in enhanced IR quality in the petroleum industry. This research contributes to stakeholder theory by providing empirical evidence supporting the role of board diversity and diligence in shaping corporate reporting practices. It also offers practical implications for companies, investors, and regulators aiming to bolster governance and transparency within the petroleum sector.